dada a função afim f(x) =2x +3, os valores de x ´para que:
a)f(x) = 1
b)f(x) = 0
c)f(x) = 1 sobre 3
pauloricardogap0o1wr:
pfv alguém ajg
Respostas
respondido por:
0
f(x) = 2x+3
a
2x+3 = 1
2x = 1-3
2x = -2
x = -2/2
x= -1
b
2x + 3 = 0
2x = -3
x= -3/2
c
2x+3 = 1/3
2x = 1/3 - 9/3
2x = -8/3
x = -8/3 . 1/2
x = -8/6
x = -4/3
a
2x+3 = 1
2x = 1-3
2x = -2
x = -2/2
x= -1
b
2x + 3 = 0
2x = -3
x= -3/2
c
2x+3 = 1/3
2x = 1/3 - 9/3
2x = -8/3
x = -8/3 . 1/2
x = -8/6
x = -4/3
respondido por:
0
Olá!!!
Resolução!!!
a)
f ( x ) = 2x + 3
1 = 2x + 3
2x + 3 = 1
2x = 1 - 3
2x = - 2
x = - 2/2
x = - 1
b)
f ( x ) = 2x + 3
0 = 2x + 3
2x + 3 = 0
2x = - 3
x = - 3/2
c)
f ( x ) = 2x + 3
1/3 = 2x + 3
2x + 3 = 1/3
2x = 1/3 - 3
2x = ( 1 - 9 )/3
2x = - 8/3
x = - 8/3 ÷ 2
x = - 8/( 3 • 2 )
x = - 8/6 : 2 = - 4/3
Espero ter ajudado!!!
Resolução!!!
a)
f ( x ) = 2x + 3
1 = 2x + 3
2x + 3 = 1
2x = 1 - 3
2x = - 2
x = - 2/2
x = - 1
b)
f ( x ) = 2x + 3
0 = 2x + 3
2x + 3 = 0
2x = - 3
x = - 3/2
c)
f ( x ) = 2x + 3
1/3 = 2x + 3
2x + 3 = 1/3
2x = 1/3 - 3
2x = ( 1 - 9 )/3
2x = - 8/3
x = - 8/3 ÷ 2
x = - 8/( 3 • 2 )
x = - 8/6 : 2 = - 4/3
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás